Let's do it safely: how Altrad Balliauw configured a package of control systems. (10th November 2016) - Bouten, Lies; Hoozée, Sophie
Abstract: This paper reports the results of a creative safety campaign introduced by a Belgian scaffolding firm to align employee behaviour at different organizational levels. Our main objective is to examine how a package of control systems can enhance safety performance. More specifically, we show how the firm's control package was configured at different organizational levels and how a safety culture was created through symbols, rituals and ceremonies. Highlights: The paper shows how a safety campaign altered the case company's safety culture. The case study investigates the operation of an effective control package. Different control systems are required for different organizational levels.